Challenges of the preceptors working with new nurses: A phenomenological research study. (September 2016) - Valizadeh, Sousan; Borimnejad, Leili; Rahmani, Azad; Gholizadeh, Leila; Shahbazi, Shahla
Abstract: Introduction: Preceptors play an important role in the transition of new nurses to the practice setting, however, preceptorship experience has been perceived as stressful by preceptors. This study aimed to explore the lived experiences of nurse preceptors working with new nurses. Method: This qualitative study used the hermeneutic phenomenological design to explore the experiences of six nurse preceptors working with new nurses in a tertiary pediatric teaching hospital in Northwest of Iran, who were recruited by purposive sampling. Data were collected using in-depth semi-structured individual interviews between July 2014 and March 2015, and analyzed using the Diekelmann's seven-stage method. Results: Data analysis revealed three themes: 1) preceptorship as a challenging and stressful role; 2) lack of support; and 3) lack of appreciation. Preceptorship as 'a challenging and stressful role' was the constitutive pattern that unified the themes. Conclusion: The preceptorship of new nurses is challenging and stressful. Preceptors endure several roles concurrently, thus, their workload should be balanced appropriately in order not to compromise with one another and evade burnout. The preceptors need to be well supported and their contribution be appropriately recognized. Setting clear objectives and realistic expectations, and having clear policies and guidelines in place should help develop a preceptorship program that is more likely to bring about positive outcomes for both preceptors and new nurses. Highlights: Acting as a preceptor for new nurses in busy clinical settings is a challenging role. Educational and mental preparation of less experienced preceptors is important. New nurse preceptors feel helplessness in the absence of support and external rewards. Getting reprimanded in the preceptorship role in the absence of favorable conditions is very stressful and unjust by the preceptors. Preceptorship should be the shared responsibility of all the members involved.